Spain in the nineteenth century : new essays on experiences of culture and society - Ginger, Andrew, 1970-; Lawless, Geraldine, 1979- (Manchester : Manchester University Press, 2018)
The nineteenth-century Hispanic world was shattered to its core by war, civil war, and revolution. At the same time, it confronted a new period of European and North-American expansion and development. In these essays, authors explore major, dynamic ways that people in Spain envisaged how they would adapt and change, or simply continue as they were. Each chapter title begins with the words "How to ... ", and examines the ways in which Spaniards conceived or undertook major activities that shaped their lives. These range from telling the time to being a man. Adaptability, paradox, and inconsistency come to the fore in many of the essays. We find before us a human quest for opportunity and survival in a complex and changing world. This wide-ranging book contains chapters by leading scholars from the United States, United Kingdom, and Spain
Introduction -- How (not) to make a durable state -- How to be universal -- How to tell time -- How to be religious under liberalism -- How to prescribe a cure for the ills of art -- How to know about right and wrong -- How to be a man -- How to be a writer for the press--and how to write about it -- How to be a cultural entrepreneur -- How to be a man of letters -- How to be an intellectual -- How to live a colonial soldier's life.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Spain -- Social conditions -- 19th century; Spain -- Civilization -- 19th century; Spain -- History -- 19th century; Espagne -- Conditions sociales -- 19e siècle.; Espagne -- Civilisation -- 19e siècle.; Espagne -- Histoire -- 19e siècle.; HISTORY -- Europe -- Spain & Portugal; LITERARY CRITICISM -- General; Civilization; Social conditions; Spain; 1800-1899; History